First combined search for neutrino point-sources in the Southern Hemisphere with the ANTARES and IceCube neutrino telescopes - Adrián-Martínez, S; Albert, A; André, M; Sarkar, S; ANTARES Collaboration; IceCube Collaboration (IOP Publishing, 2016)
We present the results of searches for point-like sources of neutrinos based on the first combined analysis of data from both the ANTARES and IceCube neutrino telescopes. The combination of both detectors, which differ in size and location, forms a window in the southern sky where the sensitivity to point sources improves by up to a factor of 2 compared with individual analyses. Using data recorded by ANTARES from 2007 to 2012, and by IceCube from 2008 to 2011, we search for sources of neutrino emission both across the southern sky and from a preselected list of candidate objects. No significant excess over background has been found in these searches, and flux upper limits for the candidate sources are presented for E -2.5 and E -2 power-law spectra with different energy cut-offs.